Identificação de doentes oncológicos idosos com necessidades de cuidados paliativos em unidades de cuidados intensivos: estudo observacional prospetivo monocêntrico - Márcio Niemeyer-Guimarães; Fermin Roland Schramm; Ricardo Tavares de Carvalho (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2018)
Introduction: Identifying factors that can help move palliative care assessments upstream appears to be potentially beneficial for older cancer patients in the critical care setting. Aim: This study aimed to determine the profile of older cancer patients admitted to the intensive care unit (ICU) and examine possible associations with criteria for a palliative care assessment. Materials and Methods: Data were collected on demographics and ICU outcome (death vs discharge) from patients aged ≥ 65 years with advanced cancer admitted to a general ICU from August 2013 to July 2014 in a single institution. Chronic conditions were scored using Charlson comorbidity index (CCI) and geriatric index of comorbidity (GIC). Severity of illness (prognosis) was assessed with simplified acute physiology score (SAPS3) and sequential organ failure assessment (SOFA), and performance status with Karnofsky performance scale (KPS) and palliative performance scale (PPS) on admission and day 7. Patients were screened for unmet palliative care needs on admission (PC1) and day 7 (PC2) using the Center to Advance Palliative Care primary/secondary criteria. Results: Of 71 patients included, 52.1% were women; mean (SD) age was 76.9 (7.1) years. GIC scores were correlated with PC1 (rs=0.326, P=0.005) and PC2 (rs=0.262, P=0.027). PC1 was correlated with prognostic scores (SAPS3: rs=0.236, P=0.047; SOFA: rs=0.263; P=0.027), while PC2 was correlated with both prognostic scores (SAPS3: rs=0.321, P=0.006; SOFA: rs=0.343, P=0.003) and performance status (KPS: rs=−0.413, P=0.0003; PPS: rs=−0.505, P=0.0001). Patients who died in the ICU (N=39, 54.9%) or were discharged (N=32, 45.1%) differed significantly in performance status (KPS, P=0.012; PPS, P=0.005), but not in prognostic scores (SAPS3, P=0.31; SOFA, P=0.41) or comorbidity indices (CCI, P=0.85; GIC, P=0.94). Conclusion: Our findings suggest that early palliative care should be integrated into intensive care to avoid potentially inappropriate interventions or procedures in older cancer patients admitted to the ICU with poor performance status and prognostic scores.